Thermal Engineering Studies with Excel, Mathcad and Internet - Ochkov, Valery; Orlov, Konstantin; Voloshchuk, Volodymyr; Rogalev, Nikolay; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides the fundamentals of the application of mathematical methods, modern computational tools (Excel, Mathcad, SMath, etc.), and the Internet to solve the typical problems of heat and mass transfer, thermodynamics, fluid dynamics, energy conservation and energy efficiency. Chapters cover the technology for creating and using databases on various properties of working fluids, coolants and thermal materials. All calculation methods are provided with links to online computational pages where data can be inserted and recalculated. It discusses tasks involving the generation of electricity at thermal, nuclear, gas turbine and combined-cycle power plants, as well as processes of co- and trigeneration, conditioning facilities and heat pumps. This text engages students and researchers by using modern calculation tools and the Internet for thermal engineering applications. .
Preamble -- Introduction -- Properties of working fluids, coolants and structural materials for thermal engineering calculations -- Working with physical quantities: Problems and Solutions -- Concentration of solutions -- My first Power Engineering Mathcad-calculation -- "Cloud" thermal dynamic algorithms -- Symbolic mathematics and 3D-graphics in thermal engineering -- Heat engineers' gift to water chemists -- Maximum water density -- NPP steam turbine cycle -- Isobar, isotherm, isochor -- Construction of direct and inverse functions on properties of working fluids on tabular data base -- Animation of thermal processes -- Calculation of Gas turbine engine cycle -- Calculation of combined (binary) cycle -- Otto cycle or what is behind the simplified formula -- Calculation of loss of pressure in the tubing -- Cogeneration (CHP), trigeneration (CCHP)and quadrogeneration (CCHPI), or how much of mathematics is contained in thermal engineering -- Differential equations in thermal engineering -- Refrigeration cycles -- Three-layer thermal engineering cake or a conclusion -- References.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Mechanical engineering; Electric power production; Engineering Thermodynamics, Heat and Mass Transfer; Mechanical Engineering; Electrical Power Engineering; Mechanical Power Engineering